Optimalisasi Pemerataan Ekonomi Islam melalui Distribusi Zakat Produktif pada Program Balai Ternak BAZNAS Siak - Aminudin Ridho; Aminatuz Zuhriyeh; Fierza Syafieqa; Sri Wigati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Economic inequality and the low level of independence among mustahik form the basis of this study. Although productive zakat has been implemented as an effort to empower beneficiaries, its application still faces challenges in terms of distribution, support, and efficiency. The BAZNAS Siak Livestock Center Program is one form of productive zakat utilization aimed at improving welfare through collective livestock management, although its contribution still requires further evaluation. This study aims to analyze the distribution of productive zakat, the program’s management mechanisms, and its impact on the income and independence of mustahik. The method used is qualitative with a descriptive literature study through journals, BAZNAS reports, and related documents. The findings indicate that the program provides positive effects in the form of increased income, skills, and independence, as well as contributing to economic equity. These results confirm that productive zakat has strategic potential when managed professionally and sustainably.